2013
DOI: 10.1590/s1516-35982013000200005
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of Nellore young bulls fed different sources of oils, protected or not from rumen degradation

Abstract: -The objective was to evaluate the addition of vegetable oils protected or not from rumen degradation in the diet of feedlot-finished young bulls and their effects on performance and carcass characteristics. Thirty-five Nellore males of 402.69±14.90 kg initial weight and 18±2 months of age were utilized. The animals were confined for 96 days, after 28 days of adaptation, and slaughtered at 532.17±30.25 kg. Experimental diets were: control (715 g total digestible nutrients -TDN/kg of dry matter -DM), with addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
1
8
0
5
Order By: Relevance
“…The addition of fat to the diet did not alter the intake of DM, CP, and neutral detergent fiber compared with the control diet. Similar results were obtained by Rosa et al (2013) in a recent study with young Nellore bulls fed different sources of fat, protected or not from rumen degradation. Diets were formulated with the same amount of protein and with a forage:concentrate ratio of 40:60, with sugarcane as the only roughage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The addition of fat to the diet did not alter the intake of DM, CP, and neutral detergent fiber compared with the control diet. Similar results were obtained by Rosa et al (2013) in a recent study with young Nellore bulls fed different sources of fat, protected or not from rumen degradation. Diets were formulated with the same amount of protein and with a forage:concentrate ratio of 40:60, with sugarcane as the only roughage.…”
Section: Discussionsupporting
confidence: 89%
“…The absence of differences (P > 0.05) between the treatments in relation to FLW and DWG is due to the level of EE in the diet in this study, and this fat concentration did not compromise animal performance. However, Rosa et al (2013) in a study in Brazil with young Nellore bulls in a feedlot concluded that the inclusion of vegetable oils, protected or not from rumen degradation, improves performance and carcass characteristics, regardless of the type of fat. DWG in this study was within the expected range.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid inclusion in ruminant diets increases the energy density and can result in better performance (Nelson et al, 2004;Rosa et al, 2013). However, fatty acids can reduce ruminal fermentability and potentially affect the performance of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fat is a popular means of increasing the energy density of diet in ruminant nutrition and can influence adipose depots and carcass composition [ 1 3 ]. Dietary fat can also be used to modify the fatty acid composition of meat and milk to fulfill the nutritional demands of consumers [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%